Islamic Religiosity and Perceived Behavioral Control on Academic Cheating - Dwi Kenia; Muhamad Uyun; Mamadou Saidou Barry (International Journal of Islamic Educational Psychology, 2023)
Cheating in education has been an issue. Students who pursue education are sometimes only value-oriented. There are many cases of students cheating on exams, committing plagiarism, and cheating on each other’s answers to get high grades. This study aims to determine the relationship between Islamic religiosity and perceived behavioral control in academic cheating. The research method used was quantitative multiple regression correlation. The research subjects were 201 active Islamic psychology students. The measuring instruments used were the Islamic Religiosity Scale (a-0.935), the Perceived Behavioral Control Scale (a-0.771), and the Academic Cheating Scale (a-0.925). The data analysis used was multiple regression. The results showed a significant negative relationship between Islamic religiosity and academic cheating and a significant relationship between perceived behavioral control and academic cheating. Islamic religiosity and perceived behavioral control contributed 51.5% to the academic cheating variable. The main conclusion is that Islamic religiosity and perceived behavioral control are related to academic cheating.